Faktor Penyebab Wanita Menunda Pernikahan di Indonesia - Usmi, Rana Sahirah; Suryani, Tania Augustine; Maharani, Reizki; Erniati, Emi; Sari, Putri Cahaya Wulan; Vania, Putri Joya; Amalia, Rahma; Putri, Gusia Alia; Norantika, Delta; Isra, Aisa (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Marriage is a sacred bond between a man and a woman that allows both parties to live together. Marriage is not only recommended by religion but is also important for a prosperous life. Marriage has a significant contribution in the personal and social development of individuals as well as in the formation of a harmonious family. Marriage is often a challenge for women as they have to balance the demands of being financially and psychologically independent with new responsibilities as partners and parents. There has been a tendency for a fairly drastic decline in marriage rates in recent years. This research focuses on the reasons or factors that influence women to postpone marriage in Indonesia. The research method used is scientific literature review research, namely reviewing and describing several articles that are accurate and relevant to the same research topic. From the research result, the factors that women delay marriage include prioritizing higher education levels, family factors, lack of mental readiness for marriage, concerns about financial conditions, fear of the risk of divorce, changes in thought patterns and the increasingly rapid influence of globalization